MODEL VEHICLE ROUTING PROBLEM DALAM MENENTUKAN BANYAKNYA RUTE DAN ARMADA PENGANGKUTAN SAMPAH DI KOTA BOGOR - Maya Widyastiti; Isti Kamila (EKOLOGIA, 2019)
Garbage problem is a common problem in urban areas, including in Bogor. This study aims to determine the number of routes and fleet of garbage transportation in Bogor. The method used is the Branch and Bound method by using the Vehicle Routing Problem model. The results obtained in the form of 69 garbage transportation routes and 36 garbage transport fleets are needed, with details of Central Bogor as many as 7 routes and 4 garbage transport fleets, North Bogor as many as 13 routes and 4 transport fleet units, East Bogor as much as 6 units 3 units of transport routes and fleets, 14 units of West Bogor and 7 units of transport fleet, 16 units of Bogor Selatan and 8 units of transport fleet, and 12 units of Tanah Sareal and 6 units of garbage transport fleet.